Susilo Bambang Yudhoyono [Indonesia, President] - Yudhoyono, Susilo Bambang (Institutional Knowledge at Singapore Management University, 2017)
The sixth President of Indonesia, Susilo Bambang Yudhoyono, tells DNA about how he handled the three economic crises and two political challenges during his two-term presidency. He stresses the importance of maintaining good personal relationships with international leaders, especially among ASEAN countries, highlighting three success factors and his hope for ASEAN.